Cyber Crimes, Their Impacts On The Users Of The Face Book And Prevention From Them In The Light Of Quran And Hadith - Sheikh Adnan Ahmed Usmani (The Islamic Culture, 2019)
The internet is a source of mass communication all over the world. Cyber-crime is the most complicated and latest problem in the cyber world. The purpose of this paper is to determine the percentage of how many people exactly know what cyber-crime is, how many people get involved in cyber-crime without knowing that it is a crime, how many users have been victim on Face book because of account hacking. Moreso it aims  to evaluate the impact on the users. In this paper after a brief introduction of information technology, cyber crimes, methods, categories of cyber criminals and prevention through government laws and policies, personal efforts in the perspective of Quran and Hadith and impact of cyber crimes on the users of the Face book. Quantitative methodology is adopted to determine the purpose of the paper for primary data. Qualitative methodology is adopted for the prevention for secondary data. 100 Face book users were selected randomly for Questionnaire and an online survey was done to collect data. Pie charts and percentages are used to display the results. The findings disclose that majority of respondents don’t know the correct definition of cyber crime and they are not even aware about the laws and punishments for cyber criminals set by the government. Results also indicates that majority of respondents care about the religious values and they don’t misuse others’ private information. Government laws and punishments are discussed and offered some suggestions by the authors.